Resonance transition X-rays generated by 800–900 MeV electrons in a periodic Mylar radiator - Kaplin V. V. Valeriy Viktorovich; Zabaev V. N. Viktor Nikolaevich; Rozum E. I.; Uglov S. R. Sergey Romanovich; Vorobiev S. A. Sergey Aleksandrovich (1993, 1993)
Title screen